Osteomedullography: a simple tool for early detection of impending non union of diaphyseal fracture of tibia - Vashisht, Arun; Swarup, Arunim (International Journal of Research in Medical Sciences, 2016)
Background: Fractures of the tibial shaft are one of the most common bony injuries to occur and are frequently associated with slow union and non-union. These fractures are commonly treated by closed reduction and internal fixation with intramedullary interlocking nail under image intensifier control. We present the results of a simple diagnostic tool the “Osteomedullography” for early detection of impending non union in diaphyseal fractures of tibia. Methods: 35 patients of diaphyseal fracture shaft tibia in which there was no clinico radiological evidence of union at 10 to 12 weeks were subjected to the diagnostic test Osteomedullography to detect the cases of impending non union at an early date. Results: The results were assessed according to the Osteomedullography signs described by Kaski (1971). Out of 35 OMG 26 (74.2%) were positive & 9 (25.8%) were found to be negative. Conclusions: OMG is a reliable, minimally invasive and economical diagnostic tool for studying the healing process of diaphyseal fractures.